Odpowiedzi

  • Użytkownik Zadane
2010-02-08T17:36:10+01:00
A)-y+8x-z-2x =-y+6x-z= -6-12+3=-15


b)-8y-4z+x-y-2z+1=-9y-6z+x+1=9-12-0,5+1=2,5


c)9y-(7y+x)+(6x-7y)=9y-7y-x+6x-7y=-5y+5x=-15-10=-25
Najlepsza Odpowiedź!
2010-02-08T17:36:46+01:00
A)-y+8x-z-2x dla x=-2,y=6,z=-3
= - 6 + 8 *(-2) - (-3) - 2*(-2)
= -6 - 16 + 3 + 4
= - 15

b)-8y-4z+x-y-2z+1 dla x=-0,5,y=-1,z=2
= - 8*(-1) - 4*2 + (-0,5) - (-1) - 2*2 + 1
= 8 - 8 - 0,5 + 1 - 4 + 1
= - 2,5

c)9y-(7y+x)+(6x-7y) dla x=-2,y=3
= 9*3 - [ 7*3 + (-2) ] + [ 6*(-2) - 7*3 ]
= 27 - ( 21 - 2) + ( -12 - 21)
= 27 - 19 + (-33)
= -25